ANALISIS TERHADAP BATASAN PEMBERLAKUAN TINDAKAN PERBUATAN MELAWAN HUKUM DAN FORCE MAJEURE DARI KERUSAKAN LINGKUNGAN AKIBAT KEBAKARAN HUTAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI NOMOR 591/PDT.G-LH/2015/PN.JKT.SEL DAN PUTUSAN PENGADILAN TINGGI NOMOR 540/PDT/2017/PT.DKI) - Nico Casey; Mella Ismelina F.R. (Jurnal Hukum Adigama, 2020)
One example of problems in environmental law that the author encountered is in the District Court Decision Number 591 / Pdt.G-LH / 2015 / PN.Jkt.Sel and the High Court Decision Number 540 / PDT / 2017 / PT.DKI which essentially contained fires forest that occurs in the Meranti Islands, which is an area belonging to PT National Sago Prima (PT NSP). In the legal considerations of the District Court judges, PT NSP was declared to have committed an illegal act which resulted in a forest fire because it was considered negligent in preventing and anticipating the forest fire. However, in the legal considerations of the High Court judges, the panel of judges has a different opinion, namely that the forest fire occurred not because of negligence by PT NSP but occurred because of a natural disaster. Then what is the basis for the judge's consideration in the limitation of enforcement of actions against the law and force majeure against environmental damage due to forest fires? Legal certainty has not been achieved due to differences in opinion regarding the status of forest fires because the Judges at the District Court and the High Court have different considerations. Apart from that, the permits required by PT NSP to run its business are also deemed non-existent, whereas in fact the permit is already owned, even though it is not yet under PT NSP's name.